HUBUNGAN PREDIABETES DENGAN ANSIETAS DAN INSOMNIA DI KLINIK PRATAMA AISYIYAH TELADAN SATU KOTA MEDAN - FEBRI NURHASANA SIREGAR; LITA SEPTINA (JURNAL ILMIAH MAKSITEK, 2021)
Prediabetes is a condition blood glucose in body is higher than normal but lower than the diabetes threshold. The prevalenceof prediabetes is higher than the prevalence of diabetes. If its not treated properly prediabetes will become diabetic within afew months or years. In patients with diabetes appear common problems that often occur namely sleep disorders and sleepdisorders may cause diabetes. Increase blood sugar levels also correlation with anxiety. To Determine the correlation ofprediabetes with anxiety and insomnia. This study used a correlative analytic cross sectional design. The study sampleconsisted of 44 prediabetes respondents, collected data using BAI and PSQI questionnaires in December 2019 - February2020. The results of the study are based on female sex 29 people (65.9%) and men 15 people (34.1%), based on work thatis not working 24 people (54.5%) and working 20 people (45.5%) , based on the results of high school education 17 people(38.6%), S1 13 people (29.6%), SMP 6 people (13.6%) and SD 8 people (18.2%), based on poor sleep quality 19 people(43.2%) and good sleep quality of 25 people (56.8% of the chi-square test results obtained Asymp Continuation correctionSig 0.010 (P> 0.05). Based on the level of mild anxiety 35 people (79.5%) and moderate anxiety level of 9 people (20.5%).Chi-square test results obtained Continuous Correction Asymp Sig 1.00 (P> 0.05).The conclusion is there significantrelationship between prediabetes with insomniaand there are no correlation between prediabetes with ansietas in aisyiyahclinic teladan satu city of Medan.